Эффективность и безопасность лечения пациентов с онихомикозом - Дюдюн, А. Д.; Гладышев, В. В.; Полион, Н. Н.; Гладышева, С. А.; Diudiun, A. D.; Gladyshev, V. V.; Polion, N. N.; Gladyshevа, S. A.; Гладишев, Віталій Валентинович; Гладишева, Світлана Анатоліївна (My University, 2018)
The purpose of this work is the development of complex differentiated treatment of onychomycosis patients with high therapeutic activity and minimal side effect. 70 ambulance and hospital patients with onychomycosis were observed. During the whole period of treatment paste of the next content, mass %: mebetizol (2-mercaptobenzthiazole) – 10.0; chinosol – 10.0; benzoic acid – 5.0; salicylic acid – 5.0; base-delivery – ad 100.0 with high antimycotic properties and good spreading has been applied on the affected nail plates topically. Starting from fifth week the terbinafine at the dose of 250 mg once a day has been prescribed till the healthy nail plates regrowth. Using of proposed by us complex therapy with high therapeutic activity allowed to decrease prescribing the systemic antimycotics for patients with onychomycosis of hands on 16±1.6; of feet on 23±2.2 days. This allows to minimize the level of systemic therapy side effects by decreasing the influence of oral drugs on hepatobiliary system and also to reduce the financial loading on the patients.
Effi cacy and safety of treatment onychomycosis patients
Keywords: feet mycosis; onychomycosis; systemic antimycotics; paste for external use; 2-mercaptobenzthiazole; chinosol; complex therapy